Work-Life Balance: An Exploratory Analysis of Family-Friendly Policies for Reducing Turnover Intentions Among Women in U.S. Federal Law Enforcement. Issue 4 (12th March 2019) - Yu, Helen H.
ABSTRACT: Recent scholarship has emphasized the influence of family-friendly policies on work attitudes such as turnover intentions. However, little research in public administration has explored the preferences of family-friendly policies or the discretionary implementation of these policies. This article provides an exploratory analysis of a U.S. federal workgroup that is less adaptive to family-care needs in response to mission requirements. Using survey data collected from 1, 111 female officers employed by a large federal law enforcement agency, work-family conflict is reported as the main reason for turnover intentions and five family-friendly policies are identified for potentially reducing turnover intentions among women. In addition, comparisons are made between female officers with children and unmarried female officers with children.